2014
DOI: 10.1371/journal.pone.0108966
|View full text |Cite|
|
Sign up to set email alerts
|

Cost-Effectiveness of Procedures for Treatment of Ostium Secundum Atrial Septal Defects Occlusion Comparing Conventional Surgery and Septal Percutaneous Implant

Abstract: ObjectivesThe study performs a cost-effectiveness analysis of procedures for atrial septal defects occlusion, comparing conventional surgery to septal percutaneous implant.MethodsA model of analytical decision was structured with symmetric branches to estimate cost-effectiveness ratio between the procedures. The decision tree model was based on evidences gathered through meta-analysis of literature, and validated by a panel of specialists. The lower number of surgical procedures performed for atrial septal def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…The budget impact analysis was conducted as an addition to the economic assessment performed by Costa et al 14 , showing that the percutaneous septal occluder was significantly more effective and less costly when compared to conventional surgery from the perspective of SUS.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The budget impact analysis was conducted as an addition to the economic assessment performed by Costa et al 14 , showing that the percutaneous septal occluder was significantly more effective and less costly when compared to conventional surgery from the perspective of SUS.…”
Section: Resultsmentioning
confidence: 99%
“…The study estimated the financial impact of the incorporation of the percutaneous septal occluder compared to conventional surgery for ostium secundum ASD, in order to provide additional information to the economic assessment by Costa et al 14 . Data on the efficacy and safety of the two procedures were obtained from a previously published systematic review 14 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“… 27 , 28 In addition, it was demonstrated that percutaneous procedures are more cost-effective and allow reducing the physical and psychological distress to the patients, as well as the operative time and hospital stay. 29 , 30 On the other hand, surgical techniques still have an advantage over percutaneous transcatheterization, in that they allow closure of larger ASDs regardless of the types and rims. 20 …”
Section: Discussionmentioning
confidence: 99%